Static Analysis for Limited Slip Differential Based on Abaqus Software - LU Lei;WANG Fei;ZHENG Quan;DAI Zhixiang (Nantong Daxue xuebao. Ziran kexue ban)
In order to obtain the specific mechanical characteristics of an anti-slip differential shell in actual working conditions, a design method based on finite element analysis for limited slip differential shell is proposed. Firstly, the finite element analysis model of limited slip differential shell is established by Abaqus software. Secondly, the force rolled in anti-slip differential case′s bearing in different working conditions are analyzed with more accurate boundary conditions and loads by using the Romax software. Then the analysis of stress, strain and fatigue are simulated. The analysis result shows that the displacement of the anti-slip differential shell is larger under extreme working conditions, which needs to be optimized. Based on the results of static analysis and taking the length and thickness of stiffeners as optimization variables, the anti-slip differential shell is optimized. By comparing the results before and after the optimization, it is found that the stress and strain of the shell under various working conditions are significantly reduced after the optimization, which meets the design requirements. The method which carries on the bearing force analysis through software simulation can effectively avoid the tedious theoretical calculation, and make the analysis method simpler and the analysis results more practical. In addition, the finite element analysis method has greatly shortened the research and development cycle and design cost of the anti-slip differential shell.